Lack of association between schizophrenia and the phospholipase-A2 genes cPLA2 and sPLA2 - Frieboes, Ralf-Michael; Henn, Fritz A. (American journal of medical genetics, 2001)
The well-established role of genetic factors in the etiology of schizophrenia together with reports of allelic association with cPLA2, a phospholipase-A2 gene, a reported increase of phospholipase-A2 activity, and the phospholipase-A2 hypothesis of Horrobin et al. [1995: Med Hypotheses 45:605-613] strongly support cPLA2 (PLA2G4A) and sPLA2 (PLA2G1B) as candidate genes for schizophrenia. In search for allelic association between these phospholipase-A2 genes and schizophrenia, two samples of Chinese and European origins, in total 328 unrelated schizophrenic patients and their parents, were investigated using Falk and Rubinstein's haplotype relative risk method. Both genes showed marginally significant evidence for association in the total sample (P ≤ 0.05), which, however, did not survive the Bonferroni correction for multiple testing. In conclusion, our results do not provide support for the phospholipase-A2 hypothesis of schizophrenia. Additional studies will be necessary to rule out a possible confounding effect of niacin sensitivity as postulated by Hudson et al. [1999: Biol Psychiatr 46:401-405]. © 2001 Wiley-Liss, Inc.